Endoscopic spray cryotherapy for genitourinary malignancies: safety and efficacy in a porcine model. (June 2013) - Power, Nicholas E.; Silberstein, Jonathan L.; Tarin, Tatum; Au, Joyce; Thorner, Daniel; Ezell, Paula; Monette, Sébastien; Fong, Yuman; Rusch, Valerie; Finley, David; Coleman, Jonathan A.
Objective: To examine the effects and safety of using endoscopic spray cryotherapy (ESC) on bladder, ureteral, and renal pelvis urothelium in a live porcine model. Subjects and methods: ESC treatments were systematically applied to urothelial sites in the bladder, ureter, and renal pelvis of eight female Yorkshire swine in a prospective trial. Freeze–thaw cycles ranged from 5 to 60 s/cycle for one to six cycles using a 7 French cryotherapy catheter. Tissue was evaluated histologically for treatment-related effects. Acute physiologic effects were evaluated with pulse oximetry, Doppler sonography, and postmortem findings. Results: In bladder, treatment depth was inconsistent regardless of dose, demonstrating urothelial necrosis in one, muscularis propria depth necrosis in two, and full thickness necrosis in all remaining samples. In ureter, full thickness necrosis was seen in all samples, even with the shortest spray duration (5 s/cycle for six cycles or 30 s/cycle for one cycle). Treatment to the renal pelvis was complicated by adiabatic gas expansion of liquid nitrogen to its gaseous state, resulting in high intraluminal pressures requiring venting to avoid organ perforation, even at the lowest treatment settings. At a planned dose of 5 s/cycle for six cycles of the first renal pelvis animal, treatment was interrupted by sudden and unrecoverable cardiopulmonary failure after three cycles. Repeated studies replicated this event. Ultrasound and immediate necropsy confirmed the creation of a large gaseous embolism and reproducible cardiopulmonary effects. Conclusion: ESC in a porcine urothelial treatment model results in full-thickness tissue necrosis in bladder, ureter, and renal pelvis at a minimal treatment settings of 5 s/cycle for six cycles. Adiabatic gas expansion may result in fatal pyelovenous gas embolism and collateral organ injury, as seen in both animals receiving treatment to the renal pelvis in this study. These results raise safety concerns for use of ESC as a treatment modality in urothelial tissues with current device settings.